Effect of mental practice using inverse video of the unaffected upper limb in a subject with chronic hemiparesis after stroke - Tanaka, Koji; Ooso, Shirou; Yamamoto, Noboru; Iso, Fumiko; Sagari, Akira; Higashi, Toshio; Tabira, Takayuki; Moriuchi, Takefumi; Iso, Naoki (Journal of Physical Therapy Science, 2016)
[Purpose] The aim of this case study was to investigate whether a method of mental practice (MP) using an inverse video of a subject’s unaffected limb to complement the vividness of motor imagery (MI) would be effective for improving affected upper limb function. [Subjects and Methods] The participant was 60-year-old male in the chronic stage of stroke recovery with left sided hemiparesis. The design of the study was AB method of Single-System-Design. He performed the MP as a home program with DVD. The intervention lasted 30 minutes a session, twice a day, 5 times a week, over 6 weeks. The DVD was created using inverse video of his unaffected upper limb. Primary outcome measures were used the Fugl-Meyer Assessment for upper limb (FMA) and the Motor Activity Log (MAL) 3 times each baseline, intervention and follow-up. The subjective vividness of MI was assessed by the Visual Analog Scale (VAS). [Results] FMA and MAL score during intervention was improved significantly comparing to baseline, and maintained in withdrawal. VAS score was improved in withdrawal comparing to baseline. [Conclusion] Results suggested that effect of mental practice for stroke patients increased by vividness of motor imagery was improved by the inverse video.